NETRALITAS APARATUR SIPIL NEGARA DAN BIROPATOLOGI DALAM PEMILIHAN KEPALA DAERAH - Umbu TW Pariangu (Universitas Halu Oleo, 2020)
The politicization of the bureaucracy cannot be separated from its mutualism character. Regional heads need electoral nutrition from ASN to win their political machine, while ASN needs political networks and closeness to power to build a career in the bureaucracy. This phenomenon will only destroy impartiality, thicken discrimination and KKN-ism in public services, shackle politics in a political remuneration cage and, no less important, reduce the value of democracy. This study method uses a qualitative method, where data is obtained using a literature review. The literature exploration in this study uses data and information sources related to the neutrality of ASN in the context of local elections in various regions and its implications for bureaucracy and democracy. Then the data is classified and analyzed.The results of the study concluded that the principle of ASN neutrality must be a fixed price, especially in the 2020 Regional Election. The ASN Commission as a partner of Bawaslu and the institution was given the authority to supervise ASN neutrality must be proactive, objectively following up on findings of violations in the field. Therefore, there is no reason for the Civil Service Officer (PPK) (regent/mayor/governor) not to impose strict sanctions on a number of ASN Commission recommendations regarding violations of ASN neutrality. The firmness of PPK in imposing sanctions will greatly help minimize “naughty” ASN.